Importance of Proactive Malaria Case Surveillance and Management in Malaysia - Liew, Jonathan Wee Kent; Mahpot, Rizawati; Dzul, Shairah; Abdul Razak, Hairul Anuar; Ahmad Shah Azizi, Noor Asmah; Kamarudin, Marina; Russell, Bruce; Lim, Khai Lone; De Silva, Jeremy Ryan; Lim, Bing Sheng; Jelip, Jenarun; Mudin, Rose Nani; et al. (American Society of Tropical Medicine and Hygiene, 2018)
Although Plasmodium vivax infections in Malaysia are usually imported, a significant autochthonous outbreak of vivax malaria was detected in a remote indigenous (Orang Asli) settlement located in northern peninsular Malaysia. Between November 2016 and April 2017, 164 cases of P. vivax infection were detected. Although 83.5% of the vivax cases were identified through passive case detection and contact screening during the first 7 weeks, subsequent mass blood screening (combination of rapid diagnostic tests, blood films, and polymerase chain reaction [PCR]) of the entire settlement (N = 3,757) revealed another 27 P. vivax infections, 19 of which were asymptomatic. The mapped data from this active case detection program was used to direct control efforts resulting in the successful control of the outbreak in this region. This report highlights the importance of proactive case surveillance and timely management of malaria control in Malaysia as it nears malaria elimination.